Accelerated kindling epileptogenesis in Tg4510 tau transgenic mice, but not in tau knockout mice. (15th July 2017) - Liu, Shijie; Shen, Yu; Shultz, Sandy R.; Nguyen, Anne; Hovens, Christopher; Adlard, Paul A.; Bush, Ashley I.; Chan, Jianxiong; Kwan, Patrick; O'Brien, Terence J.; Jones, Nigel C.
Summary: The biologic processes underlying epileptogenesis following a brain insult are not fully understood, but several lines of evidence suggest that hyperphosphorylation of tau may be an important factor in these processes. To provide further insight into the causal relationship between tau and epileptogenesis, this study applied amygdala kindling to rTg4510 mice that, concurrent with other pathologies, overexpress phosphorylated tau, tau knockout mice, or their respective wild‐type controls. Mice were electrically stimulated twice daily, 5 days per week for 3 weeks. Electroencephalography was recorded to measure the primary afterdischarge duration, and the behavioral progression of kindling‐induced seizures was assessed. rTg4510 mice (n = 10) had increased primary afterdischarge durations (p < 0.001), and significantly more rapid progression of kindling (p < 0.001), compared with wild‐type mice (n = 10). Tau knockout mice (n = 7), however, did not differ from their wild‐type counterparts (n = 8) on any of the seizure outcomes. These results suggest that Tg4510 mice are more vulnerable to epileptogenesis, but that the presence of tau itself is not necessary for kindling epileptogenesis to occur.